ANALISIS TANAH DAN PENARUH PENANAMAN UNTUK MENILAI TINGKAT KESUBURAN TANAH BEKAS GALIAN PENGRAJIN BATA MERAH DI DESA KALING KECAMATAN TASIKMADU, KABUPATEN KARANGANYAR - -, Priyono - (Eksplorasi, 2006)
ABSTRACT The research had been conducted at Kaling, Tasikmadu, Karanganyar, Central Java since April 10, 2002, until September 10, 2002. The elevation the here was 105 m above sea level and soil type was Litosol. The purpose of this research was to know the degree of the land capability and land suitability had been analysed the soil (Litosol) and the plant (Soy bean). The factorial method was used in the research based on the Randomized Completely Block Design (RCBD) with one factor of treatment four times replicated. The factor of treatment follows : 0 ton/ha (KO), 15 ton/ha (K1), 30 ton/ha (K2), 45 ton/ha (K3). Before and after planted the soil was analysed namely N-total, C-organic, P-tsd, pH, ECEC, Ca-tsd, Mg-tsd. The result of this research indicated that: 1. The dosage treatment from the waste of the sugarâ€™s manure (blotong) showed of not significant effect to all parameters observed, but showd of significant effect on the first all dry biomass.2. The result of soil analyse before planted was very low, and after planted so too.3. The highest vield was reached by treatment of K1 = 6,08 kw/ha of dry seeds, but the lowest vield was reached by treatment of K0 = 3,74 kw/ha of dry seeds. Key words : Soil analyse, plant analyse, evaluation, soil fertility, land capability, land suitability, litosol. Â